2008
DOI: 10.1002/art.23287
|View full text |Cite
|
Sign up to set email alerts
|

Defective proliferative capacity and accelerated telomeric loss of hematopoietic progenitor cells in rheumatoid arthritis

Abstract: Objective. In rheumatoid arthritis (RA), telomeres of lymphoid and myeloid cells are ageinappropriately shortened, suggesting excessive turnover of hematopoietic precursor cells (HPCs). The purpose of this study was to examine the functional competence (proliferative capacity, maintenance of telomeric reserve) of CD34؉ HPCs in RA.Methods. Frequencies of peripheral blood CD34؉,CD45؉ HPCs from 63 rheumatoid factorpositive RA patients and 48 controls matched for age, sex, and ethnicity were measured by flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 50 publications
3
81
0
3
Order By: Relevance
“…Loss of the costimulatory molecule CD28 is now recognized as a reliable aging marker on T cells (14). Subsequent studies revealed that RA T cells have shortening of telomeric sequences and that the telomeric loss affects naive, unprimed T cells as well as bone marrow precursor cells (15)(16)(17)(18)(19). Remarkably, healthy individuals typing HLA-DR4, a MHC class II haplotype associated with RA, share with patients the faster erosion of telomeres, already beginning during the second to third decades of life (16).…”
Section: Immunosenescence In Humans: Rheumatoid Arthritis As a Model mentioning
confidence: 99%
“…Loss of the costimulatory molecule CD28 is now recognized as a reliable aging marker on T cells (14). Subsequent studies revealed that RA T cells have shortening of telomeric sequences and that the telomeric loss affects naive, unprimed T cells as well as bone marrow precursor cells (15)(16)(17)(18)(19). Remarkably, healthy individuals typing HLA-DR4, a MHC class II haplotype associated with RA, share with patients the faster erosion of telomeres, already beginning during the second to third decades of life (16).…”
Section: Immunosenescence In Humans: Rheumatoid Arthritis As a Model mentioning
confidence: 99%
“…The potential significance of these subsets is detailed below. Of possible relevance to the reported differences in monocyte numbers and subpopulations in the blood of patients with RA, previous reports have described bone marrow abnormalities in RA patients, such as abnormal myeloid cells (48)(49)(50), enhanced promonocyte DNA synthesis activity (51), increased numbers of HLA-DR and CD14-positive mononuclear cells (52), high myeloid precursor numbers and CSF activity in bone marrow next to affected joints (53,54), and a defective proliferative capacity of hematopoietic progenitor cells (55).…”
Section: Mechanisms Controlling Ra Synovial Macrophage Numbersmentioning
confidence: 99%
“…Based on such observations in clinical and animal studies, it has been proposed but not yet proven that bone marrow abnormalities may even initiate and drive RA pathogenesis (48,49,55,63). In this context, the potential benefits of hematopoietic stem cell transplantation in RA have been debated (64,65), and appropriate clinical trials are needed to clarify this issue.…”
Section: Mechanisms Controlling Ra Synovial Macrophage Numbersmentioning
confidence: 99%
“…Hayflick's limit characterizes the maximum number of divisions that a single cell is able to undergo, despite telomerase activity, International Journal of Genetics and Genomics 2017; 5(5): 54-62 55 until its death. The ability of an organism to reproduce cells becomes weaker with age and with some diseases [6,7], especially those with life-threatening pathologies [8,9]. The decrease in human life span (LS) with age is accompanied by a reduction in lymphocytopoietic activity in organisms, a marked decline in the production of naïve T cells, and an increase in granulocyte numbers [7,10].…”
Section: Strongly Proliferating Cd133mentioning
confidence: 99%